Theological Education for Mission in Context Statement of a National Seminar - Chief Editor (Asian Horizons, 2008)
"Theological Education for Mission in Context" was the theme of the National Seminar, held on 20-22November 2007at Samanvaya Theological College (CMI Mission Theologate), Bhopal, Madhya Pradesh. There were 52 participants in all, consisting of formation personnel and activists of different traditional as well as frontier ministries in the Church.